Romania: Striving for Balance in the Face of Demographic Challenges - Vallasek, Magdolna (Sustainability Of The Social Security System: Demographic Challenges and Answers in Central Europe, 2023)
Long regarded as second-rate rights or disregarded in practice and implemented sparingly and partly insufficiently backed up by active, coherent measures to guarantee their exercise, social rights are coming back into focus in bad economic times. Accordingly, it is relevant to say that the question of social rights is a particularly important topic these days, as the global society faces renewed crises generated by economic recession, inflation, pandemic and war. In this context, the issue of sustainability of the social system is a key factor.This chapter presents the regulatory framework and sustainability issues of social benefits in Romania. As a starting point, we will set out the constitutional foundations and legal principles of social law and briefly outline the main stages in the development of Romanian social law regulation and the role of social law in the Romanian legal system. In the second half of the paper, we will go into more detail on some of the most important areas, such as the regulation of the pension system, accident insurance, and healthcare and longterm care, with an emphasis on demographic aspects and sustainability.KEYWORDS: social law, social benefits, demographic issues, Romania, sustainability